ArAS educational activities: history and statistics - Baleyan, G. D.; Farmanyan, S. V.; Davtyan, A. K.; Mickaelian, A. M.
A review of ArAS Educational activities is given. ArAS initiated a number of projects and events related to Astronomical Education, teacher training, as well as public activities. Among the most important are: Byurakan International Summer Schools (BISS, since 2006, 9 such schools have been accomplished), Regional Astronomical Summer Schools (RASS, since 2019, 3 such schools have been accomplished), Byurakan Summer Schools for YSU students (BSS, since 1995, 5 such events have been accomplished), ArAS School Lectures “From School to the Space” (since 2012, 11 projects have been organized), Byurakan Science Camps (BSC, since 2014, 10 events have been organized), Armenian Republican Astronomical Olympiads final phase (since 1999), a number of astronomy teacher training programs (since 2010, in total 9 events) and others. The history and statistics of all these events are presented.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture